2018
DOI: 10.1111/jir.12544
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the use of acute hospital care by people with intellectual disabilities in England

Abstract: Our figures are likely to be an underestimate as GP identification of people with ID is known to be far from complete. However, they indicate that the number of people with ID in acute hospital settings is likely to be substantially more than a recent survey of English health services indicated they were aware of. The study is intended to help guide expectations for acute hospitals seeking to audit the completeness of their identification of people with ID and to indicate their likely distribution between clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
1
29
1
Order By: Relevance
“…Our earlier paper, describing the overall pattern of hospital admissions, set out the key strengths and weaknesses of the overall study (Glover et al . ). CPRD is a well‐established data source.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our earlier paper, describing the overall pattern of hospital admissions, set out the key strengths and weaknesses of the overall study (Glover et al . ). CPRD is a well‐established data source.…”
Section: Discussionmentioning
confidence: 97%
“…This was an observational cohort study, performed as part of a wider study of hospital admission patterns for people with ID, reported elsewhere (Glover et al . ). All English NHS general practitioners (GPs) are required to keep case notes in approved computerised notes systems.…”
Section: Methodsmentioning
confidence: 97%
“…Gender and age characteristics (70% male and on average aged 43 years) reflected those with the highest presentations to ED found by Glover et al . (2019) (i.e. 57% male participants and mostly for 35–54 years), despite differences in how data were obtained (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A concern with the current study was lack of planned admission data, but this may reflect that most adults with ID come to hospital via ED, found in the United Kingdom (Glover et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation